The Effect Of Customer Orientation, Technological Orientation On Food And Beverages Business Perfomance Meditating By Customer Loyalty And Innovation Capability - Iveren Monica; Suyono Saputra; Wisnu Yuwono (UNIVED Press, 2025)
This study aims the involvement of multinational companies in a country's economy has an important role in increasing a country's per capita income. Multinational companies themselves are divided into several industrial sectors, one of which is food and beverages. This research aims to explore the impact of customer orientation and technology in increasing customer loyalty and innovation capabilities which influence the business performance of an industrial sector. The population in this study reached 280 respondents using quantitative methods. The results of this research can influence companies in making decisions and innovating considering the increase in competitors every year.